Maintenance Strategies Mapping using Decision Making Criteria Analysis in Small and Medium Industries - M.A., Burhanuddin; A.R., Ahmad; M.I., Desa (FSKSM UTM, 2007)
There are less number of machines use in small and medium industries, compared to the larger ones, which are always grouped together in serial lines. Well organized of these machines maintenance structure will ensure the effectiveness of the entire production lines. Their maintenance data should be stored to process the data, and subsequently transform them into a useful knowledge for decision making. In order to increase the effectiveness of the machines in the production lines, we have studied some decision support systems in maintenance area. Choosing and optimizing maintenance strategies is of formost importance in maintenance management. We have written a paper to identify the strategies for the machines based on 2 factors: the downtime and the frequency of machines failures with multiple criterions using decision making grid model. In this paper, we put the result obtained from the maintenance strategies implementation in one of the SMI in Malaysia. We have collected two set of raw data for the whole period of 2004, 2005 and 2006 for analysis using the model. We gave few recommendations to the maintenance crew after analyzing first dataset. Next, we compare the result after the implementation of those strategies using second dataset.